Produção de barra de cereais com propriedades probióticas - Bastos, Gustavo Almeida (2013)
The trend on the consumption of healthy, innovative and practical food is leading in the recent years, to the increase of the market of cereal bars. Cereal bar is a multicomponent product based on dry ingredients and binders, to which can be incorporated different ingredients, such as whole grain cereals, dried fruit or candied, almonds and sugars. The use of probiotic microorganisms in dairy foods is one of the most attractive options for human consumption due to its excellent functional properties. However the development of new products is becoming of increasing importance in business due to the fierce market competition and to the consumer`s demand. Thus the aim of this work was to develop formulations of cereal bars with probiotic property. Cereal bars were formulated with the probiotics Saccharomyces boulardii (in lyophilized form, granulated with lactose and encapsulated in calcium alginate) and with Lactobacillus acidophilus (in lyophilized form and encapsulated in calcium alginate). Subsequently, the stability of micro-organisms along storage time was assessed. The acceptability of the product was verified by a sensory test. The yeast Saccharomyces boulardii presented longer survival in the count of the lyophilized form. It`s count remained in the range of 7 log CFU/g for eight weeks. On the other hand encapsulated form in calcium alginate had a survival around of 6 log CFU/g for five weeks and the form granulated with lactose around of 6 log CFU/g for two weeks. The bacteria Lactobacillus acidophilus survived better in the lyophilized form. It`s count remained in the range of 7 log CFU/g for six weeks. The count of the encapsulated form after two weeks of storage was below 5 log CFU / g. The results from the sensorial analysis showed good acceptability for all formulations evaluated, in such a way that the inclusion of probiotic microorganisms in the cereal bar did not affect the structural and sensory quality of the product.